An assessment of the performance of public hearing as vehicle of public participation in infrastructure development project in Thailand - Ektewan Manowong; Ogunlana, Stephen O.; Chotchai Charoenngam; Ramachandran, Neelakantan; Soparth Pongquan; The Royal Thai Government (Pathum Thani, Thailand : Asian Institute of Technology, 2006)
Many infrastructure development projects in Thailand have recently faced unanticipated difficulties and risks during the planning and implementation stages, mainly due to social and environmental conflicts. Project delays and objections are undesirable because of the large amount of investment and associated costs involved. Public participation has increasingly become a key element to promote socially and environmentally sound development. There are wide arrays of public participation methods but public hearing is the most commonly used in many countries. Despite its popularity, public hearing has been criticized as being ineffective as a method of participation. In Thailand, public hearing was introduced only a decade ago. Project owners, mostly government agencies, employ public hearing mainly to settle disputes in projects. Public hearing in Thailand also faced problems and disruptions resulting in skepticisms on its performance. However, since there is no other official method of public participation available in Thailand, public hearing is always called for when public participation is needed. Although many attempts have been made to initiate and implement public hearing, there has been little research on the evaluation of this method of participation. Since more resources are being committed to public participation in projects, it is necessary to derive a framework for assessing public hearing conducted in Thailand's infrastructure development projects. The findings can be used to improve the effectiveness of public hearings and the quality of public inputs into project decision-making. In this study, five cases of public hearing conducted in different infrastructure projects were selected for detailed study. Public hearings in the cases were analyzed quantitatively and qualitatively. Quantitative analysis was carried out mainly by means of questionnaire survey. The questionnaire asks public hearing participants to express their attitudes toward public hearing as a means for public participation, their evaluation of the hearing they participated in, and the level of satisfaction with the hearing process and outputs/outcomes. Participants' rating on preparation and execution of public hearing performance criteria were analyzed through four aspects of public hearing process: structure of the process, participation in the process, management of the process, and resource required by the process. Apart from the five cases, secondary data on other cases of public hearing were also analyzed qualitatively using the same criteria. In the quantitative analysis of the five cases, the ANOV A test was used to explore attitudinal differences on public hearing method. Next, the Principal Component Factor Analysis was employed to group potential factors that have influence on hearing participants' evaluation and satisfaction with public hearing. Finally, the Multiple Regression Analysis was performed to investigate the level of influence of the identified underlying factors upon the hearing evaluation and satisfaction. Findings show that the public has positive attitude towards public hearing, believing that hearings provide opportunity to officially participate in projects. However, major problems are that the process is often poorly prepared and executed, making the hearing process to be of low effectiveness such that the hearing results and contributions are not satisfactory. Stakeholder consultation, information, education, participants' role and competence, hearing arrangements and facilitation, and finally, publicity and incorporation of hearing results are among the major factors that drive successful public hearing. Since positive attitude towards public hearing opens the gateway for public hearing success, achieving the performance goals and satisfying the participants would make hearings more meaningful and constructive.
A dissertation submitted in partial fulfillment of the requirements for the degree of Doctor of Engineering
Thesis (Ph.D.) - Asian Institutte of Technology, 2006
Keywords: Infrastructure (Economics) -- Developing countries; Infrastructure (Economics) -- Thaialnd